A Study on the Social Movements in Contemporary Islamic Thought - Mohammad Hossain Mokhtari (Jurnal Studi Sosial dan Politik, 2019)
Today, Islam is not restricted to the geographical borders of only a limited number of countries, but now covers the though, cultural, tribal and language borders of nations from Asia to Africa and can be counted as one of the most important and fastest growing religions in Europe and America. Whilst this spread is a means of delight, it has suffered from a type of ideological dismantling. Contemporary Islamic though can be categorized into five main groupings: 1. Anti- rational Salafism, headed by Ibn Taymiyyah and Muhammad b. Abd al-Wahab, 2. Anti –Western Religious Revivalism, headed by Sayyid Jamal al-Din Asadrabadi, 3. Anti- Religious Protestantism headed by Akhund Zadeh and Taqi Zadeh, 4. Reformist Protestantism headed by Shariati and 5. the movement of forming an Islamic civilization, led by the unique architect of the 20th century, Imam Khomeini.These schools of thought, at times contain ideas that are quite similar, but at others are extremely contradictory. It is this issue that has made research concerning these schools and ideas even more essential. Elements such as irrationality, being anti-western, reactions in the face of the waves of modernity and political theories based on religion can be mentioned as being some of the most important factors in the appearance of these trends. It is the aim of this paper to explore the backgrounds and latest developments of these thoughts over the last century in a descriptive – analytical way.